"Serc starania stracone" - szekspirowskie libretto Wystana Hugh Audena i Chestera Kallmana - Kowalski, Tomasz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
“Love’s Labour’s Lost” – Shakespearean Libretto by W.H. Auden and Ch. Kallman The article deals with the most significant changes the authors introduced in order to adapt the Shakespearean play to operatic requirements, e.g. reducing the number of characters, ascribing new parts to some of the characters remaining or balancing female and male voices on stage. An analysis is made here also of the flow of time inscribed in the libretto and the significance of the scene when the messenger comes to the Princess, saying that the King of France is dead. Their symbolism is interpreted with the additional contexts that were provided by W.H. Auden’s lecture on Love’s Labour’s Lost, which are: court love, court manners, euphuism and the Platonic philosophy and its continuations. This philosophical context allowed both poets to read the play as a process of gaining knowledge of life and feelings which the King of Navarre and his courtiers had declared to study in their academy, but never succeeded.